2020
DOI: 10.1002/pen.25486
|View full text |Cite
|
Sign up to set email alerts
|

Separation of the collagen protein by ultrafiltration: Effects of concentration on the membrane's characteristics

Abstract: Collagen is one of the predominant proteins found in all multicellular animals. In this paper, the performance of the ultrafiltration process (UF) for concentrating the collagen protein was studied by performing batch experiments using a membrane module with an effective area of 28 cm 2 and equipped with a regenerated cellulose membrane with a molecular weight cutoff of 5 kDa. The feed solution consisted of aqueous solutions of bovine collagen hydrolysate with a molecular weight of 10 kDa. The effects of feed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
0
8
1
Order By: Relevance
“…The mechanisms leading to the relation between feed concentration and UF performance were also complex to understand. Few studies observed increase of retention with feed concentrations, but this phenomenon was associated with filtration flux decrease because of pore blocking [56][57][58], which was not consistent with the present study. Liu et al have shown a recovery enhancement of MS2 and ϕX174 phages with increasing feed concentrations [10].…”
Section: Effect Of Feed Viral Concentrationcontrasting
confidence: 95%
“…The mechanisms leading to the relation between feed concentration and UF performance were also complex to understand. Few studies observed increase of retention with feed concentrations, but this phenomenon was associated with filtration flux decrease because of pore blocking [56][57][58], which was not consistent with the present study. Liu et al have shown a recovery enhancement of MS2 and ϕX174 phages with increasing feed concentrations [10].…”
Section: Effect Of Feed Viral Concentrationcontrasting
confidence: 95%
“…The filming of the cellulose acetate solution in N-methylpyrolidine (NMP) was performed at room temperature and humidity, using a certain amount of 10% polymer solution by applying it directly to a smooth glass surface (intended for thin-layer chromatography) to a thickness of 500 μm. The immersion in the ethanol-water (EW) coagulation bath in a 1:2 volume ratio was performed after a predetermined time [53,54].…”
Section: Reagents and Materialsmentioning
confidence: 99%
“…The Fourier Transform Infra-Red (FTIR) spectra obtained for the three composite membranes do not show differences in the position of the absorption bands compared to those of the base polymers [52][53][54].…”
Section: Compositional Characterization Of Membranesmentioning
confidence: 99%
“…The same extraction efficiency can also be computed based upon the absorbance of the solutions [47][48][49][50], as in:…”
Section: The Transport and Separation Of The Silver Ionsmentioning
confidence: 99%